Produksi Dan Komposisi Fisik Karkas Domba Ekor Gemuk Yang Dipelihara Secara Tradisional Di Lombok - Rr. Agustien Suhardiani; Rina Andriati; Muhamad Ashari (Faculty of Animal Husbandry, University of Mataram, 2018)
This research was conducted at the Laboratory of Cut and Work Livestock Faculty of Animal Husbandry, University of Mataram the aim was to determine the production potential of fat-tailed sheep (DEG) which includes cutting weights, carcass weight, the proportion of meat, bones, and carcass fat and carcass commercial cuts. Ten (10) sheep fat tail which consists of five adult males and five adult females used as samples. Sampling was done randomly livestock enclave fat tail sheep production in Lombok. The study was designed using a completely randomized design direction. Data collected were analyzed descriptively using average and standard deviation and percentage values according to the data categories. To find out the effect of sex on production and physical composition of the carcass, it was analyzed using t-test. At the same slaughter weight the percentage of male and female DEG carcass was significantly different (P <0.05). Female fat tail sheep produced a higher percentage of proximal thigh carcass (P <0.05) than male DEG.